Unexpected role of the steroid-deficiency protein ecdysoneless in pre-mRNA splicing - Claudius, Ann-Katrin; Romani, Patrizia; Lamkemeyer, Tobias; Jindra, Marek; Uhlirova, Mirka (PLoS genetics, 2014)
The steroid hormone ecdysone coordinates insect growth and development, directing the major postembryonic transition of forms, metamorphosis. The steroid-deficient ecdysoneless1 (ecd1) strain of Drosophila melanogaster has long served to assess the impact of ecdysone on gene regulation, morphogenesis, or reproduction. However, ecd also exerts cell-autonomous effects independently of the hormone, and mammalian Ecd homologs have been implicated in cell cycle regulation and cancer. Why the Drosophila ecd1 mutants lack ecdysone has not been resolved. Here, we show that in Drosophila cells, Ecd directly interacts with core components of the U5 snRNP spliceosomal complex, including the conserved Prp8 protein. In accord with a function in pre-mRNA splicing, Ecd and Prp8 are cell-autonomously required for survival of proliferating cells within the larval imaginal discs. In the steroidogenic prothoracic gland, loss of Ecd or Prp8 prevents splicing of a large intron from CYP307A2/spookier (spok) pre-mRNA, thus eliminating this essential ecdysone-biosynthetic enzyme and blocking the entry to metamorphosis. Human Ecd (hEcd) can substitute for its missing fly ortholog. When expressed in the Ecd-deficient prothoracic gland, hEcd re-establishes spok pre-mRNA splicing and protein expression, restoring ecdysone synthesis and normal development. Our work identifies Ecd as a novel pre-mRNA splicing factor whose function has been conserved in its human counterpart. Whether the role of mammalian Ecd in cancer involves pre-mRNA splicing remains to be discovered.
Keywords: Drosophila melanogaster; Steroids; Drosophila Proteins; sestřih RNA; RNA Splicing; mutace; proteiny Drosophily; ribonukleoproteiny malé jaderné; vývojová regulace genové exprese; Ecdysone; Gene Expression Regulation, Developmental; prekurzory RNA; Ribonucleoproteins, Small Nuclear; Spliceosomes; spliceozomy; kultivované buňky; RNA Precursors; larva; Animals; zvířata; Cell Cycle; ekdyson; Cells, Cultured; steroidy; buněčný cyklus; Larva; Mutation